Segmental redistribution of myocardial blood flow after coronary sinus reducer implantation demonstrated by quantitative perfusion cardiovascular magnetic resonance - Kevin Cheng; Francisco Alpendurada; Chiara Bucciarelli-Ducci; Jose Almeida; Peter Kellman; Jonathan M. Hill; Dudley J. Pennell; Ranil de Silva (Journal of Cardiovascular Magnetic Resonance)
ABSTRACT: Background: The coronary sinus reducer (CSR) is a novel percutaneous treatment for patients with refractory angina. Increasing evidence supports its clinical efficacy in patients with advanced epicardial coronary artery disease. However, its mechanism of action and its effects on myocardial perfusion remain undefined. Using quantitative stress perfusion cardiovascular magnetic resonance (CMR), this study assessed changes in myocardial perfusion in patients with refractory angina undergoing CSR implantation. Methods: This single-center retrospective observational cohort study included 16 patients. Rest and adenosine stress perfusion CMR was performed before and at median 5 months after CSR implantation. Perfusion images were acquired using a dual-sequence quantitative protocol with automated generation of myocardial blood flow (MBF; mL/min/g). In addition to visual assessment of ischemic segments, changes in absolute MBF across myocardial segments and between myocardial layers were analyzed. Results: A high proportion of myocardial segments had visually adjudicated ischemia at baseline (208 out of 254: 81.9%), which significantly reduced after CSR implantation (175 out of 254: 68.9%; P = 0.001). There were no changes in global MBF or strain values. Changes in myocardial perfusion reserve (MPR) correlated with baseline MPR with more ischemic segments at baseline improving to a greater extent at follow-up. Similar patterns were observed in both the left and right coronary artery territories. Changes in endocardial/epicardial MBF ratio at stress were similarly dependent on baseline values. Conclusion: In patients with refractory angina undergoing CSR implantation, quantitative stress perfusion CMR demonstrated redistribution of myocardial perfusion across segments, from less ischemic to more ischemic myocardium, and across myocardial layers with greatest improvements in endocardial perfusion observed in the most ischemic myocardium. Further studies are needed to validate the different patterns of MBF redistribution that may occur after CSR implantation and correlate with clinical outcomes.